Individual differences in environmental sensitivity: associations between cognitive emotion regulation and mental health - Yano, Kosuke; Oishi, Kazuo (Frontiers in Psychology, 2024)
Introduction: Environmental sensitivity is defined as the ability to perceive and process internal and external information. Previous studies have suggested that mental health-related factors differ by sensitivity level. This study aimed to investigate whether environmental sensitivity moderates the associations between cognitive emotion regulation strategies (e.g., rumination and blaming others) and mental health. Materials and Methods: In this three-wave longitudinal study, participants (N = 1233, 585, and 349 at Times 1, 2, and 3, respectively) completed the Cognitive Emotion Regulation Questionnaire-short and Kessler 10 scale at all the measurement points as well as the 10-item version of the Highly Sensitive Person scale and some covariates only at Time 1. Results: Latent growth model analyses indicated that the blaming others strategy had contrastive effects on changes in mental health by sensitivity level; the increase in refocusing on planning was associated with improved mental health over time only for highly sensitive individuals; and the rumination and catastrophizing strategies were the most important risk factors for mental health problems, although their effects differed slightly by sensitivity level. Conclusions: The associations between some of the cognitive strategies and mental health differ by environmental sensitivity level. Future investigations based on individual differences in sensitivity could provide innovative insights into practices.